Synthesis and physicochemical properties 4-((R))amino)-5-methyl-4H-1,2,4-triazole-3-thiols - T. V. Kravchenko; O. I. Panasenko; Ye. G. Knysh (The State Expert Center of the Ministry of Health of Ukraine, 2018)
Purposeful synthesis of derivatives of 1,2,4-triazole is one of the most important branches of modern pharmaceutical science Modern pharmaceutical market of domestic medicines requires constant updates of existing range. It makes possible the synthesis of new compounds with a predicted biological activity. The main advantage of derivatives of 1,2,4-triazole is high efficiency and low toxic. That is promising factor for creation of new chemical compounds. Analysis of literary data of past few years has showed that there is not enough information about synthesis, physical, chemical and biological properties of derivatives of 4-amino-5-methyl-4H-1,2,4-triazole-3-thiol in the literature. So synthesis and further research of derivatives of 4-amino-5-methyl-4H-1,2,4-triazole-3-thiol is topical. The research took place at the Department of toxicological and inorganic Chemistry of Zaporizhzhia State Medical University (the head of the department - professor O. I. Panasenko). During the work the research were the physicochemical properties of newly synthesized of compounds in accordance with the methods described in the State Pharmacopoeia of Ukraine. As starting substance was used 4-amino-5-methyl-4H-1,2,4-triazole-3-thiol obtained by cyclization of of potassium 2-atsetilgidrazinkarboditioata in the medium hydrazine hydrate. It is planned to research of the compounds obtained in the antimicrobial, act-protective, antioxidative and hypolipidemic activity. 9 new compounds of ylidene derivatives of 4-amino-5-methyl-4H-1,2,4-triazole-3-thiol were synthesized in a research. The structure of the new synthesized of substances was confirmed by with by means of modern of instrumental methods analysis (1H-PMR-spectroscopy, chromato-mass-spectrometry, elemental analysis). The obtained data is possible to use in purposeful synthesis for the further research of biologically active compounds.